“Constantly justifying my existence”: Lower-income, higher-weight Canadian adults’ stigma coping mechanisms - Lee Turner; Andrea E. Bombak (Qualitative Research in Medicine & Healthcare, 2024)
Individuals who are higher-weight and low-income may disproportionately experience weight and income stigmas in healthcare experiences compared to lower-weight, higher-income individuals. The ways that weight and income stigmas interact in healthcare should be better understood in order to provide better, less stigmatizing care to higher-weight, low-income patients. This study assesses how patients manage stigmatizing experiences in both healthcare and everyday experiences and how that impacts health seeking and stigma management behaviors through semistructured interviews with 11 higher-weight (Body Mass Index ≥30), low-income adults (≥18 years of age) in an Atlantic Canadian province. Participants took part in two interviews that focused on healthcare experiences and both positive and negative places/spaces. The two face-to-face interviews for each participant (total 21 interviews) were audio-recorded and professionally transcribed verbatim. The transcripts were analyzed using thematic analysis to identify recurring concepts and patterns within the data. Two major themes emerged from the data, uptake of stigmatizing, neoliberal health messaging and coping with stigma. Coping with stigma included subthemes control over stigmatizing experiences and stoicism in the face of stigma. The findings suggest that individuals understand their health and wellness through a neoliberal lens and that they deploy strategies of control and stoicism to cope with the stigmas they face.